High-strength stainless steel band and preparation method thereof
By adding specific fine crystal agents and optimizing process parameters in the preparation process of stainless steel strips, the problem of insufficient strength of stainless steel strips is solved, and its tensile strength and impact resistance are significantly improved, which is suitable for a wider range of application fields.
Patent Information
- Application Number
- CN202510196986.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The insufficient strength of existing stainless steel strips leads to prone to deformation or breaking during processing or use, affecting the quality and reliability of the product.
By adding fine crystal agents, including aluminum nitride powder, titanium powder, low-carbon iron boron powder and iron powder, in the preparation process of stainless steel strips, the composition and process parameters are optimized to improve the strength of stainless steel strips.
It significantly improves the tensile strength and impact resistance of stainless steel belts, reduces the generation and expansion of cracks, enhances the overall performance of stainless steel belts, and is suitable for a wider range of application fields.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel strips, and in particular to a high-strength stainless steel strip and a preparation method thereof. Background Art
[0002] In modern industrial production, stainless steel strips are widely used in many fields such as electronics, automobiles, aerospace, etc. due to their good corrosion resistance and machinability. However, with the continuous advancement of technology in various industries and the increasing requirements for product performance, the strength of ordinary stainless steel strips has gradually failed to meet actual needs.
[0003] If the strength of the stainless steel belt is insufficient, deformation and fracture may occur during processing or use, which seriously affects the quality and reliability of the product. Therefore, in order to broaden the scope of use of stainless steel belts, it is of great significance to develop a high-strength stainless steel belt. Summary of the invention
[0004] The invention provides a high-strength stainless steel belt and a preparation method thereof, which solves the problem of low strength of the stainless steel belt in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a method for preparing a high-strength stainless steel strip, comprising the following steps: obtaining the stainless steel strip through smelting, refining, continuous casting, hot rolling, pickling, cold rolling and annealing; During the continuous casting, a fine crystal agent is added, and the amount of the fine crystal agent added is 0.01% to 0.05% of the weight of the molten steel; The raw materials of the fine crystal agent include the following components in parts by weight: 25 parts of aluminum nitride powder, 15-30 parts of titanium powder, 4-6 parts of ferroboron powder, and 100 parts of iron powder.
[0006] As a further technical solution, the ferroboron powder is low-carbon ferroboron powder; The grades of the low carbon ferroboron powder include one or more of FeB22C0.05, FeB20C0.05, FeB18C0.1, and FeB16C0.1.
[0007] In the present invention, the inventors found that when the ferroboron powder is low-carbon ferroboron powder, it is helpful to further improve the strength of the stainless steel strip. It is speculated that by making the ferroboron powder have a lower carbon content, it is possible to avoid the formation of excessive carbides at the grain boundaries, reduce stress concentration points, and avoid the generation and expansion of cracks, thereby further improving the strength of the stainless steel strip.
[0008] As a further technical solution, when the crystal refiner is added, the superheat of the molten steel is 5-10°C.
[0009] In the present invention, when the superheat of the molten steel is 5-10° C., the crystal refiner can be better integrated with the molten steel, so that the nucleation efficiency of the crystal refiner is maximized.
[0010] As a further technical solution, the preparation method of the fine crystal agent includes the following steps: mixing the raw materials of the fine crystal agent evenly, pressing and molding, and obtaining the fine crystal agent.
[0011] In the present invention, the fine crystal agent has good shape and structural stability through compression molding, and can achieve a certain metallurgical bonding.
[0012] As a further technical solution, during the compression molding, the temperature is 1250-1350° C., the pressure is 16-20 MPa, and the time is 20-30 min.
[0013] As a further technical solution, the hot rolling includes rough rolling and finish rolling. During the rough rolling, the starting rolling temperature is 1000-1050°C, the finishing rolling temperature is 950-980°C, and the total reduction is 50%-60%. During the finish rolling, the starting rolling temperature is 850-930° C., the final rolling temperature is 800-840° C., and the total reduction is 40%-50%.
[0014] In the present invention, by optimizing the process parameters during hot rolling, the product surface can be made flat and smooth, the generation of surface defects can be reduced, and the stability of the surface quality can be ensured.
[0015] As a further technical solution, during the cold rolling, the total reduction is 35% to 50%.
[0016] In the present invention, by setting the total reduction during cold rolling to 35% to 50%, surface defects that may occur during hot rolling can be eliminated and the surface quality of the product can be improved.
[0017] As a further technical solution, the annealing includes a first stage annealing and a second stage annealing; During the first stage annealing, the holding temperature is 650-700°C for 10-15 minutes, and after the holding temperature is reduced to 500-520°C at a cooling rate of 80-100°C / h; During the second stage annealing, the holding temperature is 500-520°C, the holding time is 10-20 minutes, and after the holding, the temperature is cooled to room temperature at a cooling rate of 40-60°C / h.
[0018] In the present invention, by setting a specific annealing strategy, the work hardening of the stainless steel strip after cold rolling is eliminated, and the two-stage annealing process releases the internal stress of the stainless steel strip, thereby improving the impact resistance of the stainless steel strip.
[0019] The present invention also provides a high-strength stainless steel belt, which is prepared by the method for preparing the high-strength stainless steel belt.
[0020] As a further technical solution, the stainless steel strip is composed of the following components in weight percentage: C 0.01%~0.03%, Si 0.4%~0.6%, Mn 1.1%~1.5%, P≤0.035%, S≤0.025%, Cr 8%~10%, Ni 4%~6%, and the rest is Fe and other inevitable impurities.
[0021] In the present invention, by optimizing the composition of the stainless steel strip, the overall performance of the stainless steel strip is improved, so that it can meet the growing demand for use, and is conducive to making the stainless steel strip more widely used in a wider range of fields.
[0022] The working principle and beneficial effects of the present invention are: In the present invention, a fine crystal agent is added during continuous casting, which can promote the formation of a large number of fine grains during the solidification of molten steel, increase the grain boundary area, strongly hinder the movement of dislocations, and significantly improve the strength of the stainless steel strip. Among them, the fine crystal agent uses iron powder as a carrier, and is matched with aluminum nitride powder, titanium powder and ferroboron powder to increase the nucleation speed, while reducing the grain boundary energy and limiting the growth of grains, thereby achieving the purpose of grain refinement. In addition, the addition of ferroboron powder is also easy to improve the hot working performance of steel and improve the strength of the stainless steel strip as a whole. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the following embodiments and comparative examples, unless otherwise specified, the Fe content in the scrap steel is 98.5wt%, the Si content in ferrosilicon is 74.5wt%, the Mn content in ferromanganese is 45wt%, the Cr content in ferrochrome is 55wt%, the Ni content in ferronickel is 63wt%, the median particle size of aluminum nitride powder is 3000 mesh, the median particle size of titanium powder is 2500 mesh, the median particle size of ferroboron powder is 3000 mesh, the median particle size of iron powder is 1000 mesh, and the median particle size of boron powder is 3000 mesh.
[0025] Example 1 A method for preparing a high-strength stainless steel strip comprises the following steps: mixing scrap steel, ferrosilicon, ferromanganese, ferrochrome and ferronickel according to target composition, smelting, refining and continuous casting, adding a fine crystal agent accounting for 0.01% of the weight of the molten steel when the superheat of the molten steel is 5°C during continuous casting, then rough rolling, wherein the starting rolling temperature is 1000°C, the final rolling temperature is 950°C, and the total reduction is 50%, then finishing rolling, wherein the starting rolling temperature is 850°C, the final rolling temperature is 800°C, and the total reduction is 40%, pickling, cold rolling, wherein the total reduction is 50%, then heat preservation annealing at 700°C for 10 minutes, cooling to room temperature at a cooling rate of 70°C / h, and obtaining the stainless steel strip; The preparation method of the fine crystal agent comprises the following steps: by weight, 25 parts of aluminum nitride powder, 15 parts of titanium powder, 4 parts of ferroboron powder (ferroboron powder is medium carbon ferroboron powder, grade FeB20C0.15) and 100 parts of iron powder are ball-milled uniformly, and pressed at 1250°C and 16MPa for 30 minutes to obtain a fine crystal agent; The stainless steel strip is composed of the following components in weight percentage: C 0.01%, Si 0.4%, Mn 1.1%, P 0.035%, S0.025%, Cr 8%, Ni 4%, and the rest is Fe and other inevitable impurities.
[0026] Example 2 A method for preparing a high-strength stainless steel strip comprises the following steps: mixing scrap steel, ferrosilicon, ferromanganese, ferrochrome and ferronickel according to target composition, smelting, refining and continuous casting, adding a fine crystal agent accounting for 0.05% of the weight of the molten steel when the superheat of the molten steel is 10°C during continuous casting, then rough rolling, wherein the starting rolling temperature is 1050°C, the final rolling temperature is 980°C and the total reduction is 60%, then finishing rolling, wherein the starting rolling temperature is 930°C, the final rolling temperature is 840°C and the total reduction is 50%, pickling, cold rolling, wherein the total reduction is 35%, then heat preservation annealing at 700°C for 10 minutes, cooling to room temperature at a cooling rate of 70°C / h to obtain a stainless steel strip; The preparation method of the fine crystal agent comprises the following steps: by weight, 25 parts of aluminum nitride powder, 30 parts of titanium powder, 6 parts of ferroboron powder (the ferroboron powder is medium carbon ferroboron powder, grade FeB20C0.5) and 100 parts of iron powder are ball-milled uniformly, and pressed at 1350°C and 20MPa for 20 minutes to obtain a fine crystal agent; The stainless steel strip is composed of the following components in weight percentage: C 0.03%, Si 0.6%, Mn 1.5%, P 0.03%, S0.02%, Cr 10%, Ni 6%, and the rest is Fe and other inevitable impurities.
[0027] Example 3 The only difference between this embodiment and embodiment 2 is that in this embodiment, the ferroboron powder is low-carbon ferroboron powder with a grade of FeB20C0.05.
[0028] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the ferroboron powder is low-carbon ferroboron powder with the grade of FeB22C0.05.
[0029] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the ferroboron powder is low-carbon ferroboron powder with the grade of FeB18C0.1.
[0030] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the ferroboron powder is low-carbon ferroboron powder with the grade of FeB16C0.1.
[0031] Example 7 The difference between this embodiment and embodiment 6 is that, in this embodiment, annealing includes a first stage annealing and a second stage annealing; In the first stage of annealing, the holding temperature is 700°C, the holding time is 10 min, and then the temperature is cooled to 520°C at a cooling rate of 40°C / h; During the second annealing, the holding temperature is 520°C for 10 min, and then the temperature is lowered to room temperature at a cooling rate of 100°C / h.
[0032] Example 8 The difference between this embodiment and embodiment 6 is that, in this embodiment, annealing includes a first stage annealing and a second stage annealing; In the first stage of annealing, the holding temperature is 700°C, the holding time is 10 min, and then the temperature is cooled to 520°C at a cooling rate of 100°C / h; In the second stage annealing, the holding temperature is 520°C, the holding time is 10 min, and then the temperature is cooled to room temperature at a cooling rate of 40°C / h.
[0033] Example 9 The difference between this embodiment and embodiment 6 is that, in this embodiment, annealing includes a first stage annealing and a second stage annealing; In the first stage of annealing, the holding temperature is 650°C, the holding time is 15 min, and then the temperature is reduced to 500°C at a cooling rate of 80°C / h; During the second annealing, the holding temperature is 500°C for 20 min, and then the temperature is lowered to room temperature at a cooling rate of 60°C / h.
[0034] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the preparation method of the fine crystal agent includes the following steps: 25 parts of aluminum nitride powder, 15 parts of titanium powder and 100 parts of iron powder are ball-milled evenly by weight, and pressed at 1250°C and 16 MPa for 30 minutes to obtain a fine crystal agent.
[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, the preparation method of the fine crystal agent comprises the following steps: by weight, 25 parts of aluminum nitride powder, 4 parts of ferroboron powder (the ferroboron powder is medium carbon ferroboron powder, grade FeB20C0.15) and 100 parts of iron powder are ball-milled uniformly, and pressed at 1250°C and 16MPa for 30 minutes to obtain a fine crystal agent.
[0036] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, the preparation method of the fine crystal agent comprises the following steps: by weight, 25 parts of aluminum nitride powder, 15 parts of titanium powder, 4 parts of boron powder and 100 parts of iron powder are ball-milled uniformly, and pressed at 1250°C and 16MPa for 30 minutes to obtain a fine crystal agent.
[0037] Comparative Example 4 The only difference between this comparative example and Example 1 is that in this comparative example, no crystal refining agent is added.
[0038] Experimental Example 1 Tensile Strength Test The tensile strength of the stainless steel strips prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was tested according to GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method", wherein the test rate was 0.008 s -1 The test results are shown in Table 1 below.
[0039] Table 1 Tensile strength test results
[0040] The comparison between Example 1 and Comparative Examples 1 to 4 shows that the tensile strength of the stainless steel strip can be significantly improved by adding a fine crystal agent consisting of aluminum nitride powder, titanium powder, ferroboron powder and iron powder during continuous casting. The comparison between Example 2 and Examples 3 to 6 shows that when the ferroboron powder is low-carbon ferroboron powder, it helps to further improve the tensile strength of the stainless steel strip.
[0041] Experimental Example 2 Impact Resistance Test The stainless steel strips prepared in Examples 6 to 9 were tested for absorbed energy KV2 at room temperature according to GB / T 229-2020 "Metallic Materials Charpy Pendulum Impact Test Method", using a V-notch specimen and a 2 mm pendulum hammer blade. The test results are shown in Table 2.
[0042] Table 2 Impact resistance test
[0043] Comparison between Example 6 and Examples 7 to 9 shows that the impact resistance of the stainless steel strip is significantly improved through the two-stage annealing process.
[0044] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength stainless steel strip, characterized in that: The following steps are involved: After smelting, refining, continuous casting, hot rolling, pickling, cold rolling and annealing, a stainless steel strip is obtained; During the continuous casting, a fine crystal agent is added, and the amount of the fine crystal agent added is 0.01% to 0.05% of the weight of the molten steel; The raw materials of the fine crystal agent include the following components in parts by weight: 25 parts of aluminum nitride powder, 15-30 parts of titanium powder, 4-6 parts of ferroboron powder, and 100 parts of iron powder.
2. The method for preparing a high-strength stainless steel strip according to claim 1, characterized in that: The ferroboron powder is low-carbon ferroboron powder; The grades of the low carbon ferroboron powder include one or more of FeB22C0.05, FeB20C0.05, FeB18C0.1, and FeB16C0.
1.
3. The method for preparing a high-strength stainless steel strip according to claim 1, characterized in that: When the fine crystal agent is added, the superheat of the molten steel is 5-10°C.
4. The method for preparing a high-strength stainless steel strip according to claim 1, characterized in that: The preparation method of the fine crystal agent comprises the following steps: mixing various raw materials of the fine crystal agent uniformly, and pressing and molding to obtain the fine crystal agent.
5. The method for preparing a high-strength stainless steel strip according to claim 4, characterized in that: During the compression molding, the temperature is 1250-1350° C., the pressure is 16-20 MPa, and the time is 20-30 min.
6. The method for preparing a high-strength stainless steel strip according to claim 1, characterized in that: The hot rolling includes rough rolling and finish rolling. During the rough rolling, the starting rolling temperature is 1000-1050°C, the finishing rolling temperature is 950-980°C, and the total reduction is 50%-60%. During the finish rolling, the starting rolling temperature is 850-930° C., the final rolling temperature is 800-840° C., and the total reduction is 40%-50%.
7. The method for preparing a high-strength stainless steel strip according to claim 1, characterized in that: During the cold rolling, the total reduction is 35% to 50%.
8. The method for preparing a high-strength stainless steel strip according to claim 1, characterized in that: The annealing includes a first stage annealing and a second stage annealing; During the first stage annealing, the holding temperature is 650-700°C for 10-15 minutes, and after the holding temperature is reduced to 500-520°C at a cooling rate of 80-100°C / h; During the second stage annealing, the holding temperature is 500-520°C, the holding time is 10-20 minutes, and after the holding, the temperature is cooled to room temperature at a cooling rate of 40-60°C / h.
9. A high-strength stainless steel strip, characterized in that: The high-strength stainless steel strip is prepared by the method for preparing the high-strength stainless steel strip according to any one of claims 1 to 8.
10. The high-strength stainless steel strip according to claim 9, characterized in that: The stainless steel strip is composed of the following components in weight percentage: C 0.01%-0.03%, Si 0.4%-0.6%, Mn 1.1%-1.5%, P≤0.035%, S≤0.025%, Cr 8%-10%, Ni 4%-6%, and the rest is Fe and other inevitable impurities.
Citation Information
Patent Citations
High-speed steel alloy casting process used for roll
CN101812646A
Fine crystalline high-strength silicomanganese bainite abrasion-resistant cast steel and preparation method thereof
CN102690988A
Ferrite stainless steel grain refiner, preparation method and application thereof
CN108642241A
Preparation method of low-alloy wear-resistant steel
CN114032438A
An ultrafine grain steel sheet produced by continuous casting and rolling a medium-thin slab and its manufacture process
WO2007079625A1